Radio Constraints of Dark Matter: A Review and Some Future Perspectives - Man Ho Chan (Galaxies, 2021)
In the past few decades, many studies have analyzed the data of gamma-rays, X-rays, radio waves, electrons, positrons, anti-protons, and neutrinos to search for the signal of dark matter annihilation. In particular, analyzing radio data has been one of the most important and effective ways to constrain dark matter. In this article, we review the physics and the theoretical framework of using radio data to constrain annihilating dark matter. We also review some important radio constraints of annihilating dark matter and discuss the future perspectives of using radio detection to reveal the nature of dark matter.